1999
DOI: 10.1002/(sici)1098-2825(1999)13:6<280::aid-jcla5>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Reference distributions for the negative acute-phase proteins, albumin, transferrin, and transthyretin: A comparison of a large cohort to the world's literature

Abstract: range, in close agreement with ours where selection was based upon reported diagnosis rather than upon determination of individual health status. This meta-analysis provides support for the reliability of our recently published methodology and reference data for the clinical interpretation of individual albumin, transferrin, and transthyretin values. As with most laboratory measurements, clinical interpretation requires that other laboratory and clinical factors be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 96 publications
3
8
0
Order By: Relevance
“…The isoform-specific elevation of Igκ, HP and TTR shown in this study, supports other studies that document increased levels of IgA, IgG and inflammatory cytokines as well as increases in TTR during aging [ 93 , 96 99 ]. Decreases in PRX-2 and SAA-1 suggest metabolic dysregulation in aging mice that could contribute to accumulation of reactive oxygen species (ROS) and amyloid plaques, leading to increased cellular apoptosis [ 100 , 101 ].…”
Section: Main Textsupporting
confidence: 92%
See 1 more Smart Citation
“…The isoform-specific elevation of Igκ, HP and TTR shown in this study, supports other studies that document increased levels of IgA, IgG and inflammatory cytokines as well as increases in TTR during aging [ 93 , 96 99 ]. Decreases in PRX-2 and SAA-1 suggest metabolic dysregulation in aging mice that could contribute to accumulation of reactive oxygen species (ROS) and amyloid plaques, leading to increased cellular apoptosis [ 100 , 101 ].…”
Section: Main Textsupporting
confidence: 92%
“…The finding of 23 albumin isoforms in this study was also very striking! The fact that certain isoforms of albumin decrease specifically during the aging of C57BL/6J mouse supports other studies that show a decrease in total albumin in aging rats and humans [ 93 95 ]. Thus, differences in albumin isoforms may be a diagnostic marker of the aging mouse.…”
Section: Main Textsupporting
confidence: 86%
“…IgJ chain is a polypeptide expressed by mucosal and glandular plasma cells, which regulates formation of IgA and IgM (29). Serotransferrin is an iron-binding transport protein implicated in the innate immune response by binding free iron in the mucosa to impede bacterial survival (30). Further investigation is warranted to confirm these protein changes in larger patient cohorts and determine the functional significance to the HDL particle in the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…It is a 55-kDa homotetrameric protein which plays an important role in the transport of thyroid hormones in blood 36,52 and metabolism of retinol. 53 A scientific literature search has revealed that decreased levels of TTR have been reported in cases of severe liver diseases, malnutrition and acute inflammation [54][55][56] as well as in ovarian cancer, [57][58][59] lung cancer, 60 cholangiocarcinoma, 61 prostate cancer 62 and advanced circular and endometrial carcinoma patients, 58 but not in BC. Ours, therefore, is the first report to show that this protein is differentially expressed in breast diseases also.…”
Section: Discussionmentioning
confidence: 99%